Transformasi Digital Desa : Peningkatan Akses Pelayanan Masyarakat Melalui Pelatihan Aplikasi Di Desa Kali Deres - Martanto; Fadhil Muhammad Bsysyar; Agus Bahtiar (CV. Multi Kreasi Media, 2022)
Kali Deres Village is one of the villages in our region that has great potential for development. Despite its potential, there are several challenges that need to be overcome, including less efficient access to public services for the community. Therefore, this project aims to build and implement a community service application that will increase the efficiency and accessibility of services for village residents. Kali Deres Village may have limitations in communication infrastructure such as slow or unstable internet networks. This can hinder the accessibility and use of the app. Villagers may not have enough technological knowledge or skills to use the app effectively. Adequate training is required to ensure correct use. As a result of this community service, training participants can increase their understanding of village information systems, including the use of related software and technology. Participants can develop or update their own village information systems by utilizing the training. By utilizing an appropriate village information system, operational processes can become more efficient and effective and a good village information system can enable the provision of better and faster public services to residents.